Introduction to Belgian labour law / P. Humblet, M. Rigaux. - Humblet, P. (Patrick); Rigaux, M. (Marc) (Intersentia, 2016)
This book gives an overall picture of the principles of Belgian labour law, i.e. employment law as well as industrial relations law. It is intended for all those who want to become acquainted with Belgian labour law including foreign law firms, entrepreneurs who want to invest in Belgium, etc. For this reason the book focuses on topics that are of practical relevance.The authors not only describe and analyse the legal aspects of labour relations, but also indicate developing trends in Belgium.The book provides an up-to-date survey of the legislation that is both sufficiently detailed and usefully brief to answer most questions likely to arise in a legal setting.The authors describe all important details of the law governing working hours and wages, benefits, trade union activity, employers' associations, collective bargaining, industrial disputes, and much more.Building on a clear overview of labour law and industrial relations, the book offers practical guidance on which sound decisions in the labour law context may be based. Patrick HUMBLET is Professor of Labour Law at Ghent University. Marc RIGAUX is Professor emeritus at the Faculty of Law at Antwerp University. He was Dean of the Law Faculty from 1989 to 1993. Since 2002 he has been an assessor at the Council of State.